How Differences in Cash Transfer Sizes Affect Work Allocation Decisions: Evidence from Cross‐Country Comparisons in SSA. (4th June 2018) - Prifti, Ervin; Estruch, Elisenda; Daidone, Silvio; Davis, Benjamin
Abstract: Over the past decade, several African governments have launched Cash Transfer (CT) programmes as part of their social protection systems, with the aim of reducing poverty. Such programmes can also have significant productive impacts. We use data from four major CT programmes implemented in sub‐Saharan Africa to estimate their impacts on labour supply and demand and how effects change in relation to transfer size. We find evidence of labour reallocation between farm and off‐farm work and limited evidence of monotonicity of the labour supply–transfer size relationship.